Third Conference of Council of Muslim Librarians and Information Scientists (COMLIS III): Istanbul, Turkey Shawwal/21-23, 1409/May 24-26, 1989 (American Journal of Islam and Society, 1989)
Istanbul, the seat of the Ottoman Caliphate, was the site of the thirdmeeting of The Council of Muslim Librarians and Information Scientistsat Ataturk Cultural Center in the heart of the city. COMLIS, as the acronymimplies, is the international professional organization of librarians from Muslimcountries and communities, as well as those involved in librarianship in general.At its third meeting seven sessions were held during which a total of 28 paperswere delivered. In addition, 48 papers were submitted and included in thepublished preliminary volume of proceedings of this congress. The sevensessions were titled: The International Muslim Information Network: AConceptual Framework; Networking Models; Systems Interconnection andNetworks; Compatibility and Standardization; Establishing Centers ofExcellence in the Muslim World; Telecommunication Requirements, and;Library Cooperation. All of the papers very neatly fitted the theme of thecongress, namely "Planning an Information Strategy for the Muslim World."That the congress wa,; held under the auspices of the Turkish Ministry ofCulture's Directorate of Libraries and Publications was particularly heartening,for it symbolizes another signal of Turkey's reentry into the mainstream ofMuslim nations and communities. The arrangements of the conference weremethodical and simultaneous translations of presentations between languageswere provided .Most of the papers concentrated on what is desirable in areas ofinternational cooperation, avoidance of duplication of research, standardizationin library technology, and bi bliographical practices. No one questions thesepious aspirations, but one must go beyond what is desirable to examine whatpresently exists, and how librarianship and its associated functions can beimproved. In one of the sessions many participants addressed these veryquestions, and indeed made some very sound and practical suggestions. Atleast two papers-that of Muhammad Ali al-Tasan and Abdussattar Chaudhribothlibrarians in Saudi Arabia dealt with practical issues in librarianshipas encountered in their institutions. The conclusion one may draw from thisparticular session was that national economic and political considerationsare a big hindrance in the way of library cooperation. Librarians on their ...